Life cycle and geographic distribution of the gymnophallid Bartolius pierrei (Digenea) on the Patagonian coast, Argentina - Cremonte, Florencia (Journal of Natural History)
The life cycle of the gymnophallid Bartolius pierrei Cremonte, 2001 (Digenea) at Fracasso Beach (the type locality) (42º25’S, 64º07’W), Península Valdés, Argentina, was elucidated. This digenean uses the clam Darina solenoides (Mactridae) as both first and second intermediate host. The Kelp Gull, Larus dominicanus, and the Red Knot, Calidris canutus rufa, a Neotropical migratory bird, act as definitive hosts. A prevalence of infection of 92% was found in the Red Knot. The cercariae of B. pierrei did not parasitize other invertebrates, not even the tellinid clam Tellina petitiana, which shares the intertidal habitat with D. solenoides. This fact could be explained by the behaviour of the cercaria and its strategy for penetration. The cercariae enter directly in the extrapallial space of the clam by piercing the exposed mantle border. Tellina petitiana could not be invaded by B. pierrei cercariae because it does not expose the mantle border when feeding. Because the Red Knot does not feed on T. petitiana, this behaviour may constitute an adaptive strategy of the parasite. Under laboratory conditions, cercariae lived up to 2 days, metacercariae became infective in 50 days, and the adult life is considerd to be shorter than 3 days. The short adult life span in gymnophallids could be a result of adaptation to migratory birds. This fact would ensure parasite dispersion (i.e. by covering long distances in a short time) and inter-breeding with other Darina-infesting populations located far apart. Bartolius pierrei is an endemic parasite of the Magellan Region, distributed where its intermediate clam host is present, from San José Gulf in Península Valdés to the southern tip of South America. Fil: Cremonte, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina